Cover Image. (27th March 2018) - Obi, Naoko; Fukuda, Tetsuya; Nakayama, Noboru; Ervin, John; Bando, Yasuhiko; Nishimura, Toshihide; Nagatoishi, Satoru; Tsumoto, Kouhei; Kawamura, Takeshi
Abstract : The cover image, by Naoko Obi et al., is based on the Research Article Development of Drug Discovery Screening System by Molecular Interaction Kinetics Mass Spectrometry, DOI:10.1002/rcm.8083 .